2013
DOI: 10.1016/j.jbusres.2011.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of workplace bullying: A comparative study on six continents

Abstract: This paper is the first to explore the impact of culture on the acceptability of workplace bullying and to do so across a wide range of countries. Physically intimidating bullying is less acceptable than work related bullying both within groups of similar cultures and globally. Cultures with high performance orientation find bullying to be more acceptable while those with high future orientation find bullying to be less acceptable. A high humane orientation is associated with finding work related bullying to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
136
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(146 citation statements)
references
References 29 publications
5
136
2
3
Order By: Relevance
“…The survey is thus expected to show increasing prevalence of workplace bullying. In addition, the survey may confirm other comparative studies, such as Power et al (2013), which have shown comparatively high acceptance levels of workplace bullying among employees in Taiwan due to cultural factors.…”
Section: Expected Outcomessupporting
confidence: 72%
“…The survey is thus expected to show increasing prevalence of workplace bullying. In addition, the survey may confirm other comparative studies, such as Power et al (2013), which have shown comparatively high acceptance levels of workplace bullying among employees in Taiwan due to cultural factors.…”
Section: Expected Outcomessupporting
confidence: 72%
“…Einarsen and Hoel (2001) described three components of workplace bullying: (1) work-related bullying, such as withholding information or imposing unreasonable deadlines; (2) personal bullying, such as gossiping or spreading rumors; and (3) physical bullying, such as being shouted at or threatened with physical abuse. Work-related bullying has been shown to be the most frequent and tolerated form of bullying and is strongly related to important retention outcomes, such as turnover intent, poor mental health, and absenteeism (Berthelsen, Skögstad, Lau & Einarsen, 2011;Einarsen, Hoel, & Notelaers, 2009;Power et al, 2011).…”
Section: Turnover Intent In New Nursesmentioning
confidence: 99%
“…Bullying in the workplace unfortunately is not just a phenomenon in the U.S.; other countries are also negatively impacted by bullying, particularly workplaces in those countries with high performance, less humane, and present-oriented as opposed to future-oriented cultures (Powers, et al, 2013). Morris (2016: 261) points to a 2010 international study which indicated that 14.6% of workers are bullied at work.…”
Section: Workplace Bullying and Tort Liabilitymentioning
confidence: 99%
“…Powers, et al (2013) report on studies that indicate victims report lower wellbeing and self-esteem, less job satisfaction, depression, anxiety, irritability, more stress than other employees who are not bullied, as well as concomitant health problems. Bullying also engenders higher turnover, more absenteeism, more forced transfers and resignations, less engagement, a decline in morale, and more incivility (Richardson, Hall, and Joiner, 2016;Powers, et al, 2013;Namie, 2003). Witnesses of bullying can be adversely affected too (Powers, et al, 2013).…”
Section: Workplace Bullying and Tort Liabilitymentioning
confidence: 99%
See 1 more Smart Citation